The Role of Financial Literacy and Individual’s Behavioural Beliefs in Predicting Retirement Savings in Malaysia - @ Salleh Wahab, Mat Salleh; Abd. Karim, Mohd. Rahimie; Thien Sang, Lim (Malaysian Journal of Business and Economics (MJBE), 2018)
This paper investigates on how different level of financial literacy interacts with retirement savings in Malaysia. Alongside, the study adds mediating variable of individual behavioural beliefs, which focuses on public and private employees’ intention to accumulate regular savings for an old-age provision. The significant factors have found between advanced financial literacy and retirement savings, with the mediating effect of behavioural beliefs for that association. However, basic literacy has no sufficient impact, so does the mediating effect to support the outcome variable. Several implications have emerged: government and stakeholder’s involvements in intensifying financial educational programmes exclusively for advanced capital markets and strategic investment, offering more alternative retirement savings and investments portfolio with a higher potential growth of product, and by constantly promoting individual’s salient beliefs notably for those with an advanced literacy and propensity to save and invest for retirement adequacy. Keywords: basic financial literacy, advanced financial literacy, retirement savings, behavioural beliefs, defined contribution, defined benefit